Effects of electron doping on the d0 magnetism in N-implanted ZnO and ZnAlO films. Issue 14 (15th July 2022) - Li, Qian; Zhang, Mengdi; Yan, Weiqing; Zhang, Yifan; Liao, Bin; Zhang, Xu; Ying, Minju
Abstract: In this paper, N ions are implanted into ZnO and ZnAlO films with different carrier concentrations prepared by radio frequency reactive magnetron sputtering on sapphire substrates. The structural, electrical, optical and magnetic properties of N-doped and (Al, N) co-doped ZnO films is investigated, and the particular emphasis is placed on the effects of carrier concentration on the defects induced magnetism in the films. Our results show that all the doped ZnO films are ferromagnetic at room temperature. A trace amount of additional Al doping has a significant effect on the improvement of ferromagnetic properties, and a maximum saturation magnetization of 73 emu/cm 3 is obtained for (Al, N) co-doped ZnO films. The optical band gaps of ZnO films increase with the increasing Al doping content, which is owing to the combined effect of high carrier concentration and the Burstein Moss effect. The average transmittance of all ZnO films exceeds 80%. Our results confirm that appropriate electron doping can effectively enhance the magnetic moment in N implanted ZnO which may also apply to other ZnO systems with d 0 magnetism. Highlights: N-doped ZnO and AZO films were made by ion implantation and thus contain both N ions and defects due to implantation. The band gap and carrier concentration of ZnO films increase after Al doping. Electron doping can effectively enhance the d 0 magnetism in the N doped films. Magnetization was correlated with lattice defects and carrier concentration.